Mitogenic Effects of Brazilian Arthropod Venom on Isolated Islet Beta Cells: In Vitro Morphologic Ultrastructural and Functional Studies. (1st March 2003) - Luca, Giovanni; Calvitti, Mario; Basta, Giuseppe; Baroni, Tiziano; Neri, Luca M.; Becchetti, Ennio; Capitani, Silvano; Novaes, Geovana; Correa-Giannella, Maria Lucia; Kalapothakis, Evanguedes; Maria Engler, Sylva Stuchi; Eliaschewitz, Freddy Goldberg; et al.
Abstract : Background: One of the major pitfalls associated with use of isolated adult islets of Langerhans' cells is their minimal mitotic capacity. Consequently, maintenance of a steady viable islet cell mass is very difficult. To explore how to enhance beta-cell mitoge-nesis, we have examined the effects of venom fractions extracted from a Brazilian scorpion on morphologic and functional beta-cell patterns. The venom was previously known to induce nesidioblas-tosis-like effects with chronic hypoglycemia and pancreatitis in animal models. Methods: Venom fractions purified from Tityus bahiensis were incubated with batches of isolated rat islets, while a morphologic examination, glucose-stimulated insulin release, insulin content, and insulin messenger ribonucleic acid (mRNA) were carried out early during incubation. On fixation and double fluorescence immunolabeling (rhodamine for anti-insulin monoclonal antibodies; fluorescein for anti-5-bromodeoxyuridine), the preparations were imaged by confocal laser microscopy (CLM) for morphome- trie quantification of the mitoses. Insulin recovery and mRNA were also assessed at 21 days of culture. Results: Under CLM examination, the beta-cell mitotic rate significantly rose from 1 to 12.8% for the venom-exposed islets. At day 7, insulin release and content were significantly lower for the venom-exposed than the control islets. However, at day 21 of culture, insulin release in response to static incubation with glucose and insulin mRNA from the venom-exposed islets was higher than controls ( p < .05). Conclusions: Incubation with the scorpion venom induced a rapid and significant increase in the beta-cell proliferation not associated with a short-term increase in insulin secretion. The latter fully resumed and overcame controls later in culture, possibly after completion of the beta-cell expansion process.